Sentiment Analysis of Sarcasm in Spoken Language - Yuli Angraini (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
The objectives of the research were (1) to find out how often people used sentiment sarcasm in spoken language,(2) to know the effect of the use of sentiment sarcasm in people’s life and (3) to find out the reason why people used sentiments sarcasm when they talked to other people. The subject of the research was 26 random person consisted of native speakers and also non native speakers, specifically in public scope.The method of the research was qualitative research in the form of non participant observation. That data was collected by using interview done by the fourth semester students of Batam Center in their final semester in Speaking IV subject. All data were recorded and analyzed by using percentage. Based on 26 person’s interview, it was found that (1) 65% people often used sentiment sarcasm to other people when they wanted to be nasty and thought those people they talked too were deserved to get sentiments sarcasm from them; 25 % people did not like to use it to other people as it could hurt and put them into lowest position;and 10% people never used sentiment sarcasm at all as they chose to say directly about their intention to other people; (2) Most of people who used sentiment sarcasm to other people got the lesson of life as they had to learn to respect other people and use sentiment sarcasm in some cases only not in all situation as it brought bad effect and pain to other people who felt the impact of sentiment sarcasm; (3)There were many reasons behind sentiment sarcasm they used, but there were three most striking reason were that they wanted to give lesson to other people so they could respect people whom they talked too; to protect other’s feeling from getting hurt after revealing the truth; and to trigger their emotion that could motivate them to be a better person in life.